STRATEGIC LEADERSHIP AND ITS REFLECTION IN ACHIEVING SUSTAINABLE ORGANIZATIONAL PERFORMANCE - Anmar mudhafar Hadi Mohsen (Scholar Express Journals, 2024)
Strategic leadership has a major role in organizations, as its role comes in formulating the organization’s strategies and defining the vision and goals that the organizations seek, especially one of the most important of these goals is achieving distinguished and sustainable organizational performance. From here came the idea of this study and the problem was posed in the form of a question: Does the strategic leader have a role? In achieving sustainable organizational performance, this study aims to measure the relationship and impact between strategic leadership and sustainable organizational performance. The importance of this study is that it deals with the oil sector, which is the main artery for financing the state’s general budget, at a rate of no less than 94%, as this study assumed. The study showed that there is a relationship and influence between the strategic leader and sustainable organizational performance. In order to test this hypothesis, (100) questionnaires were developed that are suitable for analysis and were analyzed using the (spss.v.v26) program. Then, a set of results were reached, the most important of which was the existence of a positive relationship and impact of strategic leadership on sustainable organizational performance. This means that the presence of strategic leadership will enhance the achievement of sustainable organizational performance, and a set of recommendations were put forward, including emphasizing the organization under study (petroleum products) on The importance of the strategic leader because of his major role in the process of formulating strategies, staying away from routine at work, and achieving outstanding performance that enables organizations to achieve sustainable organizational performance
Keywords: Strategic Leadership; Sustainable Organizational Performance